Islam art and architecture - Hattstein, Markus; Delius, Peter (Germany H.F. Ullmann, 2007)
Follows the historical development of the Islamic dynasties and regions, showing the variety of their forms of artistic expression. This book includes decorative elements of buildings, calligraphy and the embellishment of everyday objects, as well as ornamentation.
Keywords: Islamic art; Islamic architecture; Islamic civilization